Urgensi Perluasan Pertanggungjawaban Pidana Korporasi Sebagai Manifestasi Pengejawantahan Konstitusi - Timbo Mangaranap Sirait (The Constitutional Court of the Republic of Indonesia, 2016)
The acknowledgement of Indonesia as a state of Law as mandated by Article 1 paragraph (3) of 1945 Constitution of the Republic of Indonesia is the fundamental objective of the Constitution where one of its dimensions is to create and promote fair and prosperous community, in pursuing this, with the spirit of developmentalism, the state allows the participation of corporations in the development with the hope that Indonesia will be able to compete in the globalization era. However, it is apparent that their participation has adverse impact, some of them have even been involved in bribery and corruption. According to criminal law of Indonesia, briber and receiver (gratification) will be held criminally liable. The method applied in this research is juridical normative which analyzes secondary data including secondary law materials in Criminal Code and Law No. 31/1999 in conjunction with Law 20/2001 on Corruption Eradication and United States of America of Anti-bribery Foreign Corrupt Practices Act (FCPA). Based on the analysis conducted, it was found that Indonesia can only prosecute receiver of bribery (gratification) whilst the bribing corporation is prosecuted in the United States, it is also concluded that it is urgent to expand and amend the criminal law on responsibility for corporate crime as the manifestation of constitution in the Indonesian criminal law in order to counterbalance USA Anti-bribery Foreign Corrupt Practies Act (FCPA)